PENGARUH MODEL CONTEXTUAL TEACHING AND LEARNING TERHADAP HASIL BELAJAR OPERASI HITUNG CAMPURAN BILANGAN BULAT - afrian, reni; Zuardi, Zuardi; Dalais, Mursal (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
AbstractThis study aims to determine the effect of using Contextual Teaching And Learning (CTL) model to the learning outcomes of integer mixed counting operations in V elementary grades. This type of research is quasi experimental research with non equivalent control group design. The sampling technique used is purposive sampling so sample in this research is class VA  and class VB at Elementary School 24 Panyalaian. Data collection techniques using test. Hypothesis test in this research use a t-test formula. Based on the result of research indicate that average class of CTL model equal to 74,47 and control class equal to 71,825. Based on the calculation of t test (t-test) on posttest obtained tcount (7,49312) > ttable (1,68595). This means that there is influence of using Contextual Teaching And Learning (CTL) model to student learning outcomes. Keywords: Mathematics Learning Outcomes, CTL Model